Studies on reproduction and genetic parameters of Black Bengal goat (Capra hircus bengalensis) at farmers’ field under different agro-climatic zones of West Bengal - NIANG, HEIMONMI; ROY, MANORANJAN; DATTA, SANJOY; SARKAR, UTTAM; SENAPATI, PRANAB KUMAR; BERA, SANTANU (The Indian Journal of Animal Sciences, 2021)
The present investigation was conducted on Black Bengal goat maintained in different agro-climatic clusters of West Bengal. Information from 10,348 kids born from 3,138 Black Bengal does during the period April 2010 to March 2019 reared at farmers' fields, was used to study the effect of non-genetic and genetic factors on reproduction traits. Age at first service (AFS) and age at first kidding (AFK) from 1,175 does; service period (SP) and kidding interval (KI) and litter size (LI) were considered for this study. Agro-climatic clusters, year of kidding and season of kidding were included as non-genetic factors whereas; parity of doe was taken as a genetic factor. The mean AFS and AFK were recorded to be 239.86±0.72 and 400.60±2.33 days respectively. The average SP was reported as 88.32±0.93 days, the average KI was 235.48±0.91 days and overall litter size/ kidding were 1.84±0.01 kids. Effect of cluster, season, parity and year of kidding had a significant effect on the reproduction traits. The heritability figures were 0.177±0.125, 0.147±0.118, 0.043±0.106, 0.176±0.091 and 0.182±0.138 for AFS, AFK, KI, SP and LS respectively. Low genetic and phenotypic correlations between KI and LS were observed. The does reared under the Murshidabad and Jhargram clusters showed better reproductive efficiencies than that of other clusters. Low heritability estimates obtained for all reproductive traits in the current study suggested that emphasis should be geared towards improving management practices to combat kid mortality and reduce the kidding intervals.